2000
DOI: 10.1021/ic0000653
|View full text |Cite
|
Sign up to set email alerts
|

A Dimeric Titanium-Containing Polyoxometalate. Synthesis, Characterization, and Catalysis of H2O2-Based Thioether Oxidation

Abstract: The previously unknown titanium(IV)-containing mu-hydroxo dimeric heteropolytungstate (Bu4N)7[(PTiW11O39)2-OH] (TBA salt of H1) has been synthesized, starting from H5PTiW11O40, and characterized by elemental analysis, multinuclear (31P, 17O, 183W) NMR, IR, FAB-MS, cyclic voltammetry, and potentiometric titration. 31P NMR reveals that H1 (delta -12.76) readily forms in MeCN from the Keggin monomer (POM), PTiW11O40(5-) (2, delta -13.34), upon the addition of 1.5 equiv of H+, via the protonated species, P(TiOH)W1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
122
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(131 citation statements)
references
References 89 publications
9
122
0
Order By: Relevance
“…However, Kholdeeva et al have shown that the sulfoxidation of thioethers over titanium-containing polyoxometalate catalysts is unaffected by light, oxygen or hydroquinone, indicating that radical processes are not significant. [32] Access to the pores of the catalyst may also be affected by the interfacial tension between the catalyst surface and the ionic liquid. For all the reactions performed with oxidebased catalysts in our laboratory, including the present study, the solid shows a high degree of stability with respect to particle agglomeration, and remains dispersed/suspended in ionic liquid for days.…”
Section: Discussionmentioning
confidence: 99%
“…However, Kholdeeva et al have shown that the sulfoxidation of thioethers over titanium-containing polyoxometalate catalysts is unaffected by light, oxygen or hydroquinone, indicating that radical processes are not significant. [32] Access to the pores of the catalyst may also be affected by the interfacial tension between the catalyst surface and the ionic liquid. For all the reactions performed with oxidebased catalysts in our laboratory, including the present study, the solid shows a high degree of stability with respect to particle agglomeration, and remains dispersed/suspended in ionic liquid for days.…”
Section: Discussionmentioning
confidence: 99%
“…These protonated sites play an important role in the activation of oxidants and the catalytic oxidation abilities are strongly dependent on the protonation states [95][96][97][98][99][100]102,103].…”
Section: Transition-metal-substituted Polyoxometalatesmentioning
confidence: 99%
“…In this review we would like to summarise our experience in the application of Ti-POMs for studying mechanisms of H 2 O 2 -based oxidations [130][131][132][133][134][135][136][137] and to show that these compounds can serve as a real bridge between homogeneous and heterogeneous Ti-catalysis and thus can provide mechanistic insight in surface chemistry processes. The following topics will be discussed.…”
Section: Introductionmentioning
confidence: 99%